Variability in Alternaria lini causing leaf blight disease of linseed (Linum usitatissimum L.): VARIABILITY IN ALTERNARIA LINI CAUSING LEAF BLIGHT DISEASE OF LINSEED - ANKITA SMRITI MINZ; SAVITA EKKA; H C LAL; SUPRIYA MUNDU (Journal of Oilseeds Research, 2022)
Alternaria blight is an important disease of linseed that hampers its productivity and oil content. The pathogen is geneticallydiverse showing variability in respect of cultural, morphological and pathogenic characters. Variability in seventeen isolates of Alternaria lini was carried out. Studies on cultural variability showed considerable variation among the isolates. The colony diameter varied from 46.67- 71.67 mm after 96 hrs. of incubation and most of the isolates recorded medium growth rate (50-64mm). The isolates Alt-6,Alt-7 Alt-12 showed fast growth habit (>65mm). The colony colour varied from grayish white, grey, dark olive green to grayish black. Sporulation in most of the isolates were late and concentric ring was present only in four isolates (Alt 3, Alt 8, Alt 13, Alt 14) while zonation was completely absent in other isolates. Morphologically different isolates of A. lini revealed variation with respect to mycelium width, size, shape, colour and septation of conidia. Mycelial width of most of the isolates having moderate to long width. Conidial length ranged from 24.87-33.68 mm similarly breadth of conidia ranged from7.54-10.67 mm. Transverse septation were more than longitudinal septation. Variation in beak size ranged from 3.5-6.4 mm while colour of conidia varied from brown to dark brown colour and most of the isolates exhibited obclavate, oval to obclavate shaped conidia while one isolate appeared as oval shaped. Studies on pathogenic variations revealed that the variation observed in accordance with the latent period, lesion size, lesion shape and plant disease index. The latent period of A. lini isolates varied from4.75 to 6.25 days with shortest (4.75 days) latent period recorded by isolates Alt-3 and Alt-11 and longest latent period of 6.25 days was observed in isolates Alt-6, Alt-14, Alt-16. The size of lesion varied from 2.25 to 4.75 mm and maximum lesions size (4.75 mm) was observed in isolate Alt-4 whereas minimum lesion size (2.25 mm) was observed in isolate Alt-5. The lesion produced after inoculation were elongated, oval and irregular in shape. The average number of lesions ranged from 2.75 to 4.00 with maximum number (4.00) of lesion recorded in isolate Alt-13. Plant disease index revealed that Meera and Nagarkot were more severe/virulent compare to Divya and Priyam in all the isolates.